2017
DOI: 10.1021/acs.jpca.7b02347
|View full text |Cite
|
Sign up to set email alerts
|

QTAIM and Stress Tensor Characterization of Intramolecular Interactions Along Dynamics Trajectories of a Light-Driven Rotary Molecular Motor

Abstract: A quantum theory of atoms in molecules (QTAIM) and stress tensor analysis was applied to analyze intramolecular interactions influencing the photoisomerization dynamics of a light-driven rotary molecular motor. For selected nonadiabatic molecular dynamics trajectories characterized by markedly different S state lifetimes, the electron densities were obtained using the ensemble density functional theory method. The analysis revealed that torsional motion of the molecular motor blades from the Franck-Condon poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 55 publications
(114 reference statements)
2
14
0
Order By: Relevance
“…The eigenvector‐following path with length H , see Figure B, is shorter for the S 1 compared with the S 0 as this corresponds to lower values of the ellipticity ε , see Figure A, indicating that the torsion θ is easier to perform in the excited state from the form of q i = r i + ε i e 2 , i . This finding is consistent with our earlier work with the value of the ellipticity ε of the torsion BCP being lowered by photoisomerization . The same trend is also true for the fractional lengths H f and H f θ min for the BLA and torsion θ , see Figures C,D and C,D, respectively.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The eigenvector‐following path with length H , see Figure B, is shorter for the S 1 compared with the S 0 as this corresponds to lower values of the ellipticity ε , see Figure A, indicating that the torsion θ is easier to perform in the excited state from the form of q i = r i + ε i e 2 , i . This finding is consistent with our earlier work with the value of the ellipticity ε of the torsion BCP being lowered by photoisomerization . The same trend is also true for the fractional lengths H f and H f θ min for the BLA and torsion θ , see Figures C,D and C,D, respectively.…”
Section: Resultssupporting
confidence: 92%
“…Previously, it was found that the stress tensor stiffness, S σ produced results that were in line with physical intuition . The stress tensor eigenvalue λ 3σ is associated with the bond path and previously values of λ 3σ < 0 were found to be associated with transition‐type behavior in biphenyl and molecular motors and indicated the BCP was close to rupturing and therefore we described as being unstable .…”
Section: Theory and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stress tensor eigenvalue λ 3σ is also associated with the bond‐path and previously values of λ 3σ < 0 were found to be associated with transition‐type behavior in biphenyl and molecular motors and indicated the bond critical point was close to rupturing and therefore we described as being unstable .…”
Section: Theory and Methodsmentioning
confidence: 65%
“…Theoretically, many studies have been carried out with the aim of understanding the details of the potential energy surface (PES) structures and non-adiabatic coupling (NAC) profiles to determine the rotational degrees of freedom and to simulate fast photoisomerization processes in molecular motors systems [12][13][14][15][16][17][18][19]. In contrast, the thermalization process, * ikeda.tatsushi.37u@kyoto-u.jp † A.G.Dijkstra@leeds.ac.uk ‡ tanimura.yoshitaka.5w@kyoto-u.jp which is known as a rate-limiting step of molecular motors [6][7][8], has not been well explored.…”
Section: Introductionmentioning
confidence: 99%